2011
DOI: 10.1021/ol200196m
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Mediated Palladium-Catalyzed Direct C−H Arylation of 3-Bromoisothiazole-4-carbonitrile

Abstract: Silver(I) fluoride-mediated Pd-catalyzed C-H direct arylation/heteroarylation of 3-bromoisothiazole-4-carbonitrile (1a) gives twenty-four 5-aryl/heteroaryl-3-bromoisothiazole-4-carbonitriles. The reaction was partially optimized with respect to catalyst, ligand, and base. During this study 3,3'-dibromo-5,5'-biisothiazole-4,4'-dicarbonitrile (3a) was isolated as a byproduct and subsequently prepared via the silver-mediated Pd-catalyzed oxidative dimerization of 3-bromoisothiazole-4-carbonitrile in 67% yield. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In particular, the alkylation of C5 on functionalized isothiazoles, while previously observed, has only been reported for a limited substrate scope. 19 …”
Section: Resultsmentioning
confidence: 99%
“…In particular, the alkylation of C5 on functionalized isothiazoles, while previously observed, has only been reported for a limited substrate scope. 19 …”
Section: Resultsmentioning
confidence: 99%
“…Additive salts were found to have al arge impact on the reaction efficiency( entries [12][13][14][15]. Use of either Pd(OAc) 2 or [Pd(dba) 2 ]( dba = dibenzylideneacetone) instead of [PdCl 2 (MeCN) 2 ]l ed to as lightly diminished yield (entries 5a nd 6).…”
Section: Methodsmentioning
confidence: 99%
“…Building upon their studies on cross‐coupling reactions of isothiazoles, in 2011, Koutentis and co‐workers described the first direct C−H arylation method of isothiazoles (Scheme ) . They found that the use of PdCl 2 (PPh 3 ) 2 (5 mol%) as a catalyst, AgF (3 equiv.)…”
Section: Reactivity Of Isothiazolesmentioning
confidence: 99%